(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
The large amount and variety of data available on the web creates the opportunity of applying data mining techniques on the Internet, this is known as web-mining. When a person needs to find some information on the web, usually they will resort to some search engine, and one of the biggest problems is finding the relevant data among so many search results to be able to extract useful knowledge. Therefore, techniques are needed to increase the efficiency of responses, since people have different standards of preferences and activities they perform online. Such patterns and data about users can be “mined” to make the user’s own experience on some website more efficient. This article aims to explain the basic concepts necessary to understand the theme of web-mining.